Quality, functionality, and microbiology of fermented fish: a review. Issue 7 (11th April 2020) - Zang, Jinhong; Xu, Yanshun; Xia, Wenshui; Regenstein, Joe M.
Abstract: Fermentation is a traditional food preservation method and is widely used for improving food safety, shelf life, and organoleptic and nutritional attributes. Fermented fish are produced and consumed in different parts of the world and are an integral part of many food cultures. Furthermore, fermented fish are a source of interesting microbes and are an important industry in many countries. This review tries to update the types and manufacturing processes for fermented fish around the world. The emphasis is on this work related to fermented fish and their health benefits, as well as the contribution of microorganisms to their fermentation. A variety of different approaches have been used to determine and understand microbial composition and functionality. Moreover, some challenges and future research directions regarding fermented fish are also discussed in this review. Further research into fermented fish products is of crucial importance not only for the food industry but also for human health. However, extensive in vivo and toxicological studies are essential before the application of bioactive-rich fermented fish products for human health benefits.